Modulating the morphology of hydrogel particles by thermal annealing: mixed biopolymer electrostatic complexes. (29th September 2015) - Wu, Bi-cheng; McClements, David Julian
Abstract: Biopolymer hydrogel particles formed by electrostatic complexation of proteins and polysaccharides have various applications within the food and other industries, including as delivery systems for bioactive compounds, as texture modifiers, and as fat replacers. The functional attributes of these electrostatic complexes are strongly influenced by their morphology, which is determined by the molecular interactions between the biopolymer molecules. In this study, electrostatic complexes were formed using an amphoteric protein (gelatin) and an anionic polysaccharide (pectin). Gelatin undergoes a helix-to-coil transition when heated above a critical temperature, which impacts its molecular interactions and hydrogel formation. The aim of this research was to study the influence of thermal annealing on the properties of hydrogel particles formed by electrostatic complexation of gelatin and pectin. Hydrogel particles were fabricated by mixing 0.5 wt% gelatin and 0.01 wt% pectin at pH 10 (where both were negatively charged) at various temperatures, followed by acidification to pH 5 (where they have opposite charges) with controlled acidification and stirring. The gelation ( ) and melting temperature ( ) of the electrostatic complexes were measuring using a small amplitude oscillation test: °C and °C. Three annealing temperatures (5, 30 and 50 °C) corresponding to different regimes (, , and ) were selected to control the configuration of the gelatin chain. The effects of formation temperature, annealing temperature, and incubation time on the morphology of the hydrogel particles were characterized by turbidity, static light scattering, and microscopy. The results of this study will facilitate the rational design of hydrogel particles with specific particle dimensions and morphologies, which has important implications for tailoring their functionality for various applications.